Cohort study of electronic cigarette use: effectiveness and safety at 24 months. Issue 3 (6th June 2016) - Manzoli, Lamberto; Flacco, Maria Elena; Ferrante, Margherita; La Vecchia, Carlo; Siliquini, Roberta; Ricciardi, Walter; Marzuillo, Carolina; Villari, Paolo; Fiore, Maria
Abstract : Objective: To evaluate the safety and effectiveness of e-cigarettes, by comparing users of only e-cigarettes, smokers of only tobacco cigarettes and dual users. Design: Prospective cohort study. We update previous 12-month findings and report the results of the 24-month follow-up. Data sources: Direct contact and questionnaires by phone or via internet. Methods: Adults (30–75 years) were classified as: (1) tobacco smokers, if they smoked ≥1 tobacco cigarette/day, (2) e-cigarette users, if they inhaled ≥50 puffs/week of any type of e-cigarette and (3) dual users, if they smoked tobacco cigarettes and also used e-cigarettes. Carbon monoxide levels were tested in 50% of those declaring tobacco smoking abstinence. Hospital discharge data were used to validate possibly related serious adverse events in 46.0% of the sample. Main outcome measures: Sustained abstinence from tobacco cigarettes and/or e-cigarettes after 24 months, the difference in the number of tobacco cigarettes smoked daily between baseline and 24 months, possibly related serious adverse events. Results: Data at 24 months were available for 229 e-cigarette users, 480 tobacco smokers and 223 dual users (overall response rate 68.8%). Of the e-cigarette users, 61.1% remained abstinent from tobacco (while 23.1% and 26.0% of tobacco-only smokers and dual users achieved tobacco abstinence). The rate (18.8%) of stopping use of either product (tobacco and/or e-cigarettes) was not higher for e-cigarette users compared with tobacco smokers or dual users. Self-rated health and adverse events were similar between all groups. Among those continuing to smoke, there were no differences in the proportion of participants reducing tobacco cigarette consumption by 50% or more, the average daily number of cigarettes and the average self-rated health by baseline group. Most dual users at baseline abandoned e-cigarettes and continued to smoke tobacco. Those who continued dual using or converted from tobacco smoking to dual use during follow-up experienced significant improvements in the 3 outcomes compared with those who continued or switched to only smoking tobacco (p<0.001). Conclusions: E-cigarette use alone might support tobacco quitters remaining abstinent from smoking. However, dual use did not improve the likelihood of quitting tobacco or e-cigarette use, but may be helpful to reduce tobacco consumption. Adverse event data were scarce and must be considered preliminary. Trial registration number: NCT01785537.